Neuromuscular fatigue in pitchers across a collegiate baseball season - Stone, B. L.; Schilling, B. K. (The Journal of Strength and Conditioning Research, 2020)
Neuromuscular fatigue in baseball pitchers has become an important aspect of injury risk. It is imperative to understand how fatigue is manifested to enhance resiliency and mitigate injury risk. Secondarily, collecting data on neuromuscular characteristics of baseball pitchers provides a framework to address these concerns. Using the countermovement jump, this study observed neuromuscular performance during the preseason, midseason, and postseason of a collegiate baseball season with college baseball pitchers. No statistically significant changes were noted in any of the main variables at any testing timepoint (p > 0.05). However, several variables, including concentric mean force (ConMF, d = 0.59) and concentric peak force (ConPF, d = 0.59) in addition to eccentric mean force (EccMF, d = 0.54) and eccentric mean power (EccMP, d = -0.66), displayed moderate effects from preseason testing to midseason testing. Furthermore, jump height displayed a large negative effect from preseason to midseason (d = -0.89). Secondarily, descriptive data for both concentric and eccentric variables were also determined from the present findings. There were moderate changes in neuromuscular fatigue in Division I collegiate pitchers across a competitive season and has provided descriptive data for neuromuscular characteristics in collegiate baseball pitchers.